2003
DOI: 10.1097/00004770-200308000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Objective Measurement of Patient’s Dental Anxiety by Galvanic Skin Reaction

Abstract: The purpose of this study was to determine if anxiety can be measured objectively by skin conductance of a weak electric current. Three measurements were taken. First, a standardized dental-anxiety questionnaire was given to determine anxiety. Second, galvanic skin conductance was measured. Third, polygraph responses were recorded to three key questions from the questionnaire. Questionnaire scores of these key questions were used to create two groups: anxious and not-anxious. The three key questions were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 7 publications
1
17
0
Order By: Relevance
“…In accordance with our findings, several studies have shown a relationship between self-reported measures of dental anxiety and skin conductance in adults (10,14,24). It has been shown that in the highly-anxious patients the correlations among scores are stronger.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In accordance with our findings, several studies have shown a relationship between self-reported measures of dental anxiety and skin conductance in adults (10,14,24). It has been shown that in the highly-anxious patients the correlations among scores are stronger.…”
Section: Discussionsupporting
confidence: 93%
“…The GSR uses psycho-physiological measurements to quantitate levels of anxiety in patients (10). The first step of validation was to compare GSR with the fully recognized scales of anxiety i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relationship between emotion and SCR has been investigated in dental research, where a statistically significant correlation was found between SCR and the degree of dental anxiety. 24 It was also reported that high-fear participants responded with significantly larger SCRs during threat periods than low-fear participants. 25 The goal of the present study was to investigate individual differences in the autonomic response to acupuncture stimulation and its relationship to fear of acupuncture, including possible pain and possible adverse events.…”
Section: Introductionmentioning
confidence: 95%